Rio Lobo - Wayne, John, 1907-1979.; O'Neill, Jennifer; Elam, Jack, 1916-; Mitchum, Chris (Beverly Hills, CA : FoxVideo, 1992)
In this post-Civil War drama, a former Union officer is hunting the two traitors responsible for the death of his best friend. The trail leads him to the lawless town of Rio Lobo, Texas.
VHS format.
"7016"
Rated G.
Original story by Burton Wohl.
Videocassette release of the 1970 motion picture.
Closed captioned for the hearing impaired.
Keywords: Feature films; Western films; Video recordings for the hearing impaired; Videocassettes; West (U.S.) -- Motion pictures